Kakas Bantu Perhitungan Kompleksitas Perangkat Lunak Menggunakan Metrik Cognitive Weighted Inherited Class Complexity - Widyawati Widyawati; Bayu Priyambadha; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Software maintenance is a software development phase that requires more effort, time, and cost. One of the causes of maintenance problems is the high value of software complexity. Developers will find it difficult to understand the software when doing maintenance or if there are changes. In the Object Oriented approach (OO) the use of inheritance, encapsulation, coupling, polymorphism, etc. can facilitate developers in building software. However, the use of high inheritance can also result in high values ​​of complexity. Manually calculating the complexity of a lot of software requires a lot of time and resources. Therefore, it is easy to help calculating software complexity using the Cognitive Weighted Inherited Class Complexity (CWICC) ​​metric. CWICC metrics are OO metrics that function to calculate the complexity of software based on an understanding of the attributes, methods, and inheritance of a class. This system has been built on the programming language of Java and also has been tested using unit testing and integration testing that uses whitebox testing and validations testing that use blackbox testing. This system has an accuracy of 100% and the time for calculating with system is 356 times more faster than with manually.